Integration of Islamic Studies on Reproductive Physiology at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Hasibuan, Hotmaidah (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The aim of this research is to analyze the integration of Islamic studies in the study of the biology of the human reproductive system at the Syekh Ali Hasan Ahmad Addary Padangsidimpuan National Islamic University. This research uses a qualitative descriptive approach through field research, using an integrated scientific and Islamic approach through verses from the Al-Qur’an about reproductive physiology.The results and discussion of this research show that the learning process implemented has not fully achieved the integration of science and Islam in biology learning. This can be seen from the results of a questionnaire conducted by the Whatss group of 20 students which was distributed to the 6th semester biology student group, that every sub-discussion of material related to the reproductive system previously had not fully integrated uluhiyah learning. information contained in the Koran. The process has not been completely perfected. This research recommends the integration of science and Islam in Islamic higher education studies. The moral message instilled in students is not only about learning biology as a secular science, but can also increase awareness about the integration of scientific research in the world and the future.